2022
DOI: 10.1128/jvi.01622-21
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Soluble gp130/Spike-Nanobody Fusion Protein Simultaneously Blocks Interleukin-6 trans -Signaling and Cellular Infection with SARS-CoV-2

Abstract: SARS-CoV2 infection can induce mild to life threatening symptoms. Especially individuals over 60 years of age or with underlying co-morbidities including heart or lung disease, and diabetes or immune compromised patients are at higher risk. Fatal multi-organ damage in COVID19 patients can be attributed to Interleukin (IL-)6 dominated cytokine storm. Consequently, IL-6R monoclonal antibody treatment for severe COVID19 cases has been approved for therapy. High concentrations of soluble IL-6R were found in COVID1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(125 reference statements)
1
3
0
Order By: Relevance
“…Thus, we focused our attention on further developing NB26 that bound at a highly conserved occluded region on the capsid and showed had therapeutic potential. Here, we found that NB26 modifications into an Fc-linked Nanobody improved binding affinities and increased neutralization capacities, as has been found to improve biochemical functions and inhibition for viruses such as HIV and COVID-19 (42)(43)(44)(45)(46). Our structural data suggests that Fc-NB26 could bind most GII genotypes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, we focused our attention on further developing NB26 that bound at a highly conserved occluded region on the capsid and showed had therapeutic potential. Here, we found that NB26 modifications into an Fc-linked Nanobody improved binding affinities and increased neutralization capacities, as has been found to improve biochemical functions and inhibition for viruses such as HIV and COVID-19 (42)(43)(44)(45)(46). Our structural data suggests that Fc-NB26 could bind most GII genotypes.…”
Section: Discussionsupporting
confidence: 56%
“…S5). Similar modifications have improved inhibition capacities for viruses such as HIV and COVID-19 (42)(43)(44)(45)(46). A direct ELISA was used to evaluate the cross-reactive binding capacity of Fc-NB26 with numerous GII genotypes (GII.4, GII.8, GII.10, GII.14, GII.17, GII.24, GII.28, and GII.NA1) (Fig.…”
Section: An Engineered Fc-linked Nanobody (Fc-nb26)mentioning
confidence: 99%
“…6 ). This sgp130 variant is composed of cs130Fc functionalized with an additional neutralizing single-domain antibody to the SARS-CoV-2 spike protein, yielding an IL-6 trans-signalling inhibitor with high binding affinity for both IL-6–sIL-6R complexes and the SARS-CoV-2 spike protein 155 . Importantly, c19s130Fc was shown to inhibit SARS-CoV-2 infection of cells and to improve the therapeutic efficacy of sgp130Fc, indicating that c19s130Fc may provide synergistic therapeutic effects on containing viral infection and the resulting hyperinflammation.…”
Section: Next-generation Inhibitors Of Il-6 Trans-signallingmentioning
confidence: 99%
“…c19s130Fc is a bispecific therapeutic that hinders both the IL-6 signaling pathway and the SARS-CoV-2 RBD. It is created by fusing a soluble cytokine receptor with an antiviral Nb, enabling it to block viral entry and dampen the inflammatory response induced by the virus simultaneously ( 165 ). In addition, researchers have engineered exosomes with a S-protein-targeting Nb and human IFN-β bound to MFG-E8, creating a dual-action system.…”
Section: Challenges and Current Countermeasuresmentioning
confidence: 99%